Injection of the Sphenopalatine Ganglion With C-Arm And Radiofrequency For Trigeminal Neuralgia - Satriyanto, Muhammad Dwi; Ketut Ngurah Gunapriya; Ristiawan Muji Laksono; Saiful Anwar (Greenation Publisher & Yayasan Global Research National, 2024)
Trigeminal Neuralgia (TN) is the most severe pain in the world, where patients experience a painful condition from the face that significantly impacts the quality of life and socio economic function of affected patients. The pathophysiology of TN is still unclear, it is thought that TN occurs due to compression of the root entry zone of the trigeminal nerve near the origin of the brain stem and this local pressure causes demyelination which leads to abnormal depolarization which results in ectopic impulses. The sphenopalatine ganglion is a parasympathetic ganglion that is connected to the trigeminal, facial, and sympathetic systems and consists of somatosensory, sympathetic, and parasympathetic nerve fibers. This ganglion receives sensory impulses from around the face. TN Management can in a way pharmacological and surgical; however, it is not capable in a way of effectively relieving, since the technology of radiofrequency ablation, TN patients can be done with radiofrequency ablation with satisfactory results, even one daycare.